Synthesis of some oxopyrano-oxazine compounds from the reactions of malonyl with organonitriles - Hussain, Faiq H. S.; Hawaiz, Farouq E. (Sulaimani Journal for Pure and Applied Sciences, 2000)
The reaction of malonyl chloride with RCN (R: Cyclopentyl , CHPU2 , C6II3BTF) at 100 C" and room temperature yielded pyrimidine derivatives , 2(R: Cyclopentyl ) and oxopyrano oxazine derivatives 4(R,cyclopentyl ; CHphz, Cd{jBrF) respectively , The structures of these products have been determined by elemental analysis and spectroscopic methods